2012
DOI: 10.1007/s11999-011-2075-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique: A Cup-in-Cup Technique to Restore Offset in Severe Protrusio Acetabular Defects

Abstract: Background Severe medial and/or superior defects encountered in revision THA are currently managed with jumbo (C 66 mm) acetabular components and modular augments, with reconstruction cages, or with the cup-cage technique. Preoperative planning can indicate when these techniques may not restore vertical and horizontal offset. Failure to restore offset can lead to impingement, leg length inequality, abductor weakness, and dislocation. Surgical Technique We developed a ''cup-in-cup'' technique in which a porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In this setting, a second porous metal shell, placed in appropriate inclination and anteversion, is cemented into the first shell. Early results show no failures in eight hips, but the average follow-up time was less than two years 25 .…”
Section: Technique By Paprosky Classificationmentioning
confidence: 87%
“…In this setting, a second porous metal shell, placed in appropriate inclination and anteversion, is cemented into the first shell. Early results show no failures in eight hips, but the average follow-up time was less than two years 25 .…”
Section: Technique By Paprosky Classificationmentioning
confidence: 87%
“…Previously published studies have reported the application of cup-in-cup technique in the management of severe protrusio acetabular defects. [3][4][5] In comparison, the cup-on-cup First, the creation of initial stability and the anchoring concepts are different. Cup-in-cup technique using two porous tantalum acetabular cups: one larger medial cup is placed on to supportive host bone in a cementless fashion to buttress large defects, establish the initial stability, increase the horizontal offset and restore the vertical offset.…”
Section: Discussionmentioning
confidence: 99%
“…While our early clinical measures are promising, longer follow-up is needed to determine if cement debonding and loosening risks increase as loading and torsional stresses accumulate over time from the longer moment arm created by increasing leg length and offset. 14,20 In cases of acetabular component malposition, the cup-incup construct can be used selectively in cases where substantial retroacetabular bone loss exists, and cup explantation would cause imminent discontinuity and/or drastically alter the surgeon's ability to reconstruct the socket due to loss of superomedial support. Previously placed cups in a neutral orientation or mild retroversion (no more than 10°) are not necessarily excluded as long as they meet the minimum dimensions requirement, and the degree of their malposition does not cause further impingement when the new inner cup is placed in the targeted position (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…17 Offset was measured on an anteroposterior (AP) radiograph of the affected hip using the technique described by Berstock et al 18 and Merle et al 19 For the cup-in-cup radiographs, horizontal offset was designated as a horizontal line connecting the mid-point of the best fitting circle of the prosthetic head and the ilioischial line. 20 Leg length ("vertical offset") estimates were determined on AP pelvis radiographs as the perpendicular difference in millimeters between a line connecting the inferior aspect of the ischial tuberosities and the most prominent medial tip of the lesser trochanter. 21 Basic statistical analysis using Fisher's exact testing was conducted to analyze categorical data pre-and postoperatively given our small sample size.…”
Section: Methodsmentioning
confidence: 99%